The Process of Group Psychotherapy: Systems for Analyzing Change.
DOI: 10.1037/10378-009
|View full text |Cite
|
Sign up to set email alerts
|

The Group Development Process Analysis Measures.

Abstract: The Group Development Process Analysis Measures were designed to facilitate the study of development in small groups. The measures include three scales for the process analysis of verbal content and style dimensions, a set of speech behavior codes, and a sociometric test for the identification of emergent leaders. The primary focus of this chapter is on the process analysis scales and the speech behavior measures. The process analysis scales are (a) the Hostility/Support Scale; (b) the Experiencing Scales (Kle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Yalom (1995) addressed group development but did not use it as a specific framework for formulating interventions. Emphasizing that the task of group therapy is influenced by the group's development, Beck (Beck, 1981; Lewis, Beck, Dugo, & Eng, 2000) developed a theory of group development with nine phases. Rutan and Stone (1993) devoted a chapter in their text to group development and group dynamics and suggested that group therapists gain a deeper understanding by knowing the stages of group development.…”
mentioning
confidence: 99%
“…Yalom (1995) addressed group development but did not use it as a specific framework for formulating interventions. Emphasizing that the task of group therapy is influenced by the group's development, Beck (Beck, 1981; Lewis, Beck, Dugo, & Eng, 2000) developed a theory of group development with nine phases. Rutan and Stone (1993) devoted a chapter in their text to group development and group dynamics and suggested that group therapists gain a deeper understanding by knowing the stages of group development.…”
mentioning
confidence: 99%
“…At Category Seven, a sustained expansion of awareness is apparent, with continued movement from one inner referent to others. A more detailed description and definition of the scale categories with examples of ratings can be found in training manuals by Klein [18].…”
Section: Instrumentationmentioning
confidence: 99%